The influence of internet as an academic tool in the development of second language acquisition in students of Intensive Intermediate English courses from the Foreign Language Department at the University of El Salvador, year 2018 - Menéndez López, Mirta Betsai (2024)
New methodologies, resources, techniques, approaches and technologies are becoming more and more popular at the time of teaching and learning a foreign language. In all these interaction with new ways of teaching and learning, the internet is becoming probably the most used and reliable tool that offers an almost unlimited source of resources to improve the second language acquisition. Thus, the interaction, use or integration of internet as an academic tool is becoming more and more necessary. Institutions all over the world are implementing new methodologies based on internet to improve or make the learning process more attractive and convenient not only for students but also for educators. Different types of academic platforms, social networks, general websites,authentic material and many other examples of resources are offered by this technology. This, at the same time requires relying on the access of equipment that allows controlling the use of technology with an academic purpose. Academies and other institutions that offer the opportunity to learn a foreign language are evolving and updating their resources in order to take advantage of this technology. By doing so, they not only assure a close interaction between the and the student but they also offer a wide variety of tools and opportunity for the students to improve their skills.